Polar Riometer Observations. - Cormier,Raymond J. (1970)
Qualitative descriptions of the morphology of Polar Cap Absorption (PCA) events are given, using data from the following riometer stations: Thule and Godhavn, Greenland; Churchill Range, Manitoba, Canada; and Reykjavik (Leirvogur), Iceland. The dependence of commencement time on solar zenith angle and subsequent daily variations in absorption following the initial day are described. The morphology of PCA events is very important for forecasting the behavior of ionospheric absorption during a PCA event. It is shown that besides information concerning the energy spectrum of the proton flux, the season and time of day must also be considered for forecasting the expected absorption. (Author)